Business and society : ethics and stakeholder management - Carroll, Archie B.; Buchholtz, Ann. (Cincinnati, Ohio ; London : South-Western ; International Thomson, 1999)
This book is divided into four parts: Business, Society and Stakeholders; Business ethics and management; External stakeholder issues; and Internal Stakeholder issues.
Keywords: Business; Management; Industrial management -- Social aspects; Industrial management -- Social aspects -- Case studies; Social responsibility of business; Social responsibility of business -- Case studies